Stenting versus Bypass Surgery for the Treatment of Left Main Coronary Artery Disease - Park, Seung-Jung (Yonsei University College of Medicine, 2009)
Based on data comparing coronary-artery bypass grafting (CABG) with medical therapy, the current guidelines recommend CABG as the treatment of choice for patients with left main coronary artery (LMCA) disease. Percutaneous coronary intervention (PCI) can be selectively performed in patients who are candidates for revascularization but who are ineligible for CABG. Current evidence indicates that stenting results in mortality and morbidity rates compared favorably with those seen after CABG. Data from several extensive registries and a large clinical trial may have prompted many interventional cardiologists to choose PCI with stenting as an alternative treatment option for such patients. In addition, these data may inform future guidelines and support the need for well-designed, adequately powered, prospective, randomized trials comparing the two revascularization strategies.